Advancing the Careers of Military Spouses An Assessment of Education and Employment Goals and Barriers Facing Military Spouses Eligible for MyCAA - Friedman, Esther M. (RAND Corporation, 2015)
The authors compare recent users and nonusers of My Career Advancement Account (MyCAA), a scholarship program for eligible military spouses pursuing associate's degrees, occupational certificates, or licenses in portable career fields. Through survey data, they investigate program use and nonuse and educational and employment experiences, preferences, and barriers. They conclude with recommendations for the Department of Defense.